A community-based study on knowledge and awareness of chronic obstructive pulmonary disease at Bagan Serai, Perak - Mohd Danee, Muhammad Faizudeen; Mohammed Yusri, Nur Syafiqah (2018)
Nowadays in Malaysia, Chronic Obstructive Pulmonary Disease (COPD) is one of the diseases that commonly occur among Malaysian other than asthma and most of the people do not aware about the disease. The main objective of the study was to identify the knowledge and awareness of COPD among the public. The respondents were conveniently approach and the total subjects that had been participated in this study were 305. This research used constructed questionnaire to collect data regarding knowledge and awareness of COPD as well as the factors associated with knowledge and awareness of COPD. This study was conducted at Bagan Serai specifically at Parit Haji Ismail 3 Village, Alor Kubu Village and Parit Mat Keling Village. This study revealed that most of the respondents achieved moderate level of knowledge and awareness with 206 (67.5%) and 178 (58.4%) respondents respectively. Furthermore, this study reported that knowledge and awareness does not affected by gender and age group. However, in association with smoking status, knowledge shows no relationship with it but there is an association with awareness.